Du haut de leurs mansardes : le motif de l’isolement chez Baudelaire et Xavier de Maistre - Vittorio Fortunati (Revue Italienne d'Etudes Françaises)
Charles Baudelaire’s poem Paysage (Les Fleurs du Mal, LXXXVI) bears odd similarities to Xavier de Maistre’s Expédition nocturne autour de ma chambre (1825): the choice of an intimate place of isolation (a loft), the view of the urban landscape and the starlit sky, the role of imagination and daydreaming. However, there is not enough evidence that Baudelaire read the Expédition nocturne. In fact, an intertextual comparison of the texts underlines the differences between the two writers, which largely correspond to those characterizing the time periods in which they lived.